Neighborhood group chats as a subject of offline sociology - Ivanov, K. A. (Cifrovaâ sociologiâ, 2023)
Neighborhood group chats have become an inseparable attribute of most urban localities. Despite their significant role in the processes of neighborhood communication and the construction of local communities, this phenomenon has been little comprehended by social science. The purpose of this article is to offer variants of adaptation of some sociological approaches to the analysis of the phenomenon of neighborhood chats. The nature of neighborhood chat as an institutional and communication-oriented tool for information exchange is described. The classification of neighborhood chats according to the level of their closeness is given. The forms of control in the selection of participants in closed versions of neighborhood chats are explained. The communicative side of neighborhood chat is proposed to be considered through the prism of E. Goffman’s “dramaturgy”. Conceptualizations of the basic concepts of “dramaturgy” in the context of digital neighborhood interaction are proposed. The complicated nature of neighborhood chat as a technological and social phenomenon is analyzed using the actor-network theory approach. The identification of neighborhood chat as an “actor-network” has been substantiated. The functional side of neighborhood chat as a mechanism of assemblage of neighborhood communities is considered in correlation with R. Oldenburg’s concept of the “third place”. It is shown that the neighborhood chat, being rather a digital simulation of the “third place”, can potentially compensate for the lack of real public spaces in the conditions of typical development, launching and supporting the processes of integration on the locality.